1977
DOI: 10.1007/bf02124102
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate fertilizers as environmental pollutants: Positive correlation between nitrates (NaNO3 and KNO3) used per unit area and stomach cancer mortality rates

Abstract: Since a significant positive correlation between nitrate fertilizer exposure and stomach cancer mortality has been found, a study of nitrate fertilizer pollution in arable land in terms of amount of nitrates used per unit area (kg/ha) and stomach cancer death rates was carried out. The regression of death rates for stomach cancer, standardized for age, on the nitrates used per unit area, by province (N = 25), exhibited a significant association between the 2 variables (p less than 0.004). When industrialized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…Epidemiológica! studies have shown a link between the incidence of gastric cancer and the amount of NO 3 ingestion (191) and the use of (exposure to) nitrogen fertilizers (192)(193)(194). However, if we consider that nitrogen fertilizers may …”
Section: Thiamin (Vitamin Bj)mentioning
confidence: 94%
“…Epidemiológica! studies have shown a link between the incidence of gastric cancer and the amount of NO 3 ingestion (191) and the use of (exposure to) nitrogen fertilizers (192)(193)(194). However, if we consider that nitrogen fertilizers may …”
Section: Thiamin (Vitamin Bj)mentioning
confidence: 94%
“…Nitrate exposure has been positively correlated with the incidence of stomach cancer in 12 countries (Hartman, 1983) and in specific areas of several other countries, including UK, Colombia, Chile, Denmark, Hungary and Italy (Hill et al, 1973;Cue110 et al, 1976;Zaldivar, 1977;Juhasz et al, 1980;Amadori et al, 1980). However, other studies have shown no correlation, or even an inverse correlation, between nitrate exposure and the incidence of stomach cancer (Davies, 1980;Armijo et al, 1981;Forman et al, 1985).…”
Section: Nitrate Exposure Endogenous Nitrosation and Stomach Cancermentioning
confidence: 99%
“…N-nitroso-compounds can be formed endogenously in humans; they have been identified in vivo in the stomach, in the infected urinary bladder and in saliva and faeces [Fraser et al, 1980]. In epidemiological studies, gastric cancer risk was linked to nitrogen (fertilizer) usage in Chile [Armijo & Coulson, 1975;Zaldivar, 1977;Zaldivar & Wetterstrand, 1975] and to the nitrate concentration in well-water in Colombia [Cuello et al, 1976;Tannenbaum et al, 1979]. Case-control studies in Japan and among Japanese migrants to Hawaii [Haenszel et al, 1972] have linked gastric cancer risk to certain food items, and to well-water use in Japan ].…”
Section: Introductionmentioning
confidence: 99%